2023
DOI: 10.1136/bcr-2022-254402
|View full text |Cite
|
Sign up to set email alerts
|

Rapid progression of probable Creutzfeldt-Jakob disease with concomitant COVID-19 infection

Adrian McGrath,
Hari Pai,
Aidan Clack

Abstract: A previously healthy man in his 80s was admitted to a district general hospital with rapidly progressing dementia, gait abnormalities and myoclonus alongside COVID-19 infection. Investigations showed mild elevation of C-reactive protein and neutrophils, unremarkable CT head and mildly raised protein in cerebrospinal spinal fluid (CSF). Brain MRI revealed bilateral cortical and striatal diffusion restriction and electroencephalogram (EEG) findings showed diffuse activity slowing with high amplitude sharp/slow-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Durin one of the worst global pandemics of the last century, caused by the COVID-19 disease under the persistent immune pressure exerted by the newest vaccines, the SARS-CoV virus is fast mutating and becoming less severe but more contagious. On the other hand some studies [7][8][9] indicate that elderly COVID-19 patients, or those who have reported virulent episode of this infection, experience some long-lasting neurological complica tions, including encephalopathy, encephalitis, cerebrovascular disease, Parkinson' disease (PD), Alzheimer's disease (AD), and prion disease (PrD). Before the COVID-1 outbreak, the principal cause of rapidly progressive dementia was certainly prion disease excluding infectious, metabolic, vascular, neoplastic, and autoimmune disorders Nowadays, a growing number of studies demonstrated that patients surviving COVID 19 can show the neuroinflammatory activation of microglia and astrocytes that migh favor the fast development of neurodegenerative diseases, such as CJD [9].…”
Section: Discussionmentioning
confidence: 99%
“…Durin one of the worst global pandemics of the last century, caused by the COVID-19 disease under the persistent immune pressure exerted by the newest vaccines, the SARS-CoV virus is fast mutating and becoming less severe but more contagious. On the other hand some studies [7][8][9] indicate that elderly COVID-19 patients, or those who have reported virulent episode of this infection, experience some long-lasting neurological complica tions, including encephalopathy, encephalitis, cerebrovascular disease, Parkinson' disease (PD), Alzheimer's disease (AD), and prion disease (PrD). Before the COVID-1 outbreak, the principal cause of rapidly progressive dementia was certainly prion disease excluding infectious, metabolic, vascular, neoplastic, and autoimmune disorders Nowadays, a growing number of studies demonstrated that patients surviving COVID 19 can show the neuroinflammatory activation of microglia and astrocytes that migh favor the fast development of neurodegenerative diseases, such as CJD [9].…”
Section: Discussionmentioning
confidence: 99%